Analysing Mental Health Problems among Pregnant Women: A Literature Review - Marya Yenita Sitohang (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2023)
This study aims to investigate evidence on perinatal mental health problems in low-middle income countries (LMICs). Pregnancy that changes women’s physical condition may give unexpected mental health burden to women during and after the pregnancy. While prevalence of perinatal mental health problems higher in LMICs than developed countries, exploration of this issue in LMICSs is still limited. Using narrative literature review, this study provides critical analysis on existing literature about perinatal mental health problems. Findings shows the prevalence of perinatal mental health problems in LMICs is quite high with complex risk factors. Risk factors for pregnant women experiencing mental health problems can come from individuals, families, and communities, including biological and social factors. Social factors determine perinatal mental health problems often related to gender. Therefore, this study proposes gender analysis of perinatal mental problems in LMICs and how gender transformative approach can contribute to promote health of mothers, fathers, and children during the perinatal period.